A calculus problem by Alf-archie Sangkula

Calculus Level 2

A real-valued function f satisfies the equation f ( x ) + f ( 1 1 x ) = x x 1 f(x) + f (\dfrac{1}{1-x})= \dfrac{x}{x-1} for all real numbers x 0 , 1 x\ne0, 1 . Find 24 × f ( 3 ) 24 \times f(-3)

61 45 56 67

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

For this problem, since we need the value of f(-3), it is a good idea to substitute x = -3 and see what happens:

f ( 3 ) + f ( 1 1 ( 3 ) ) = 3 3 1 , f ( 3 ) + f ( 1 4 ) = 3 4 . ( 1 ) \begin{aligned} f(-3) + f \left( \frac{1}{1-(-3)} \right) &= \frac{-3}{-3-1},&& \\ f(-3) + f\left( \frac{1}{4} \right) &= \frac{3}{4}. &&-(1) \end{aligned}

From the equation above, we will know the value of f(-3) once we know the value of f ( 1 4 ) f \left( \frac{1}{4} \right) . So let’s repeat the step above! (Repeating steps is a common problem solving technique…) Substituting x = 1 4 x = \frac{1}{4} into the original functional equation:

f ( 1 4 ) + f ( 1 1 1 4 ) = 1 4 1 4 1 , f ( 1 4 ) + f ( 4 3 ) = 1 3 . ( 2 ) \begin{aligned} f \left(\frac{1}{4}\right) + f \left( \frac{1}{1-\frac{1}{4}} \right) &= \frac{\frac{1}{4}}{\frac{1}{4}-1},&& \\ f \left( \frac{1}{4} \right) + f\left( \frac{4}{3} \right) &= -\frac{1}{3}. &&-(2) \end{aligned}

Again! Substituting x = 4 3 x = \frac{4}{3} into the original functional equation:

f ( 4 3 ) + f ( 1 1 4 3 ) = 4 3 4 3 1 , f ( 4 3 ) + f ( 3 ) = 4. ( 3 ) \begin{aligned} f \left(\frac{4}{3}\right) + f \left( \frac{1}{1-\frac{4}{3}} \right) &= \frac{\frac{4}{3}}{\frac{4}{3}-1},&& \\ f \left( \frac{4}{3} \right) + f\left( -3 \right) &= 4. &&-(3) \end{aligned}

Our persistence has paid off! Taking (1) + (3) - (2):

2 f ( 3 ) = 3 4 + 4 ( 1 3 ) , 24 f ( 3 ) = 9 + 48 + 4 = 61 . \begin{aligned} 2f(-3) &= \frac{3}{4} + 4 - \left( -\frac{1}{3} \right), \\ 24f(-3) &= 9 + 48 + 4 \\ &= \boldsymbol{61}. \end{aligned}

The answer is 61.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...